PERSEPSI GURU PAMONG TENTANG KETERAMPILAN DASAR MENGAJAR MAHASISWA PPL-2 DI SMA SWASTA PONTIANAK TENGGARA - Anggraini, Gita; Asriati, Nuraini; Genjik S, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the Basic Teaching Skills of PPL-2 Students in FKIP Economic Education Pontianak Untan Academic Year 2018/2019 which implements PPL 2 in Southeast Pontianak Private Hig h School. The method in this study was descriptive with the Study Survey research form. The data sources of this study are 4 Civil Servant Teachers from the Economic Education Students who are PPL in Southeast Pontianak Private High Schools and interview data with tutors. The results of the research conducted showed 1) Explaining skills in very good categories (87.5%), 2) Skill of holding Variations in good categories (74.99%), 3) Asking skills in less categories (50%), 4) Skills managing classes in a fairly good category (55%). Then, it can be concluded that the Basic Teaching Capability of FKIP UNTAN Economic Education Students implementing PPL-2 Academic Year 2018/2019 in Southeast Pontianak Private High School according to the Teachers' Perception in the category is quite Good (66.75%). Keywords: Teacher's Perception, Basic Teaching Skills, PPL-2 Students